Trace-mineral salt for steers on an all-roughage ration (Concrete shelter vs. dirt and no shelter) - McCarter, M.M.; Koch, B.A.; Smith, E.F.; Richardson, D. (Kansas Agricultural Experiment Station, 2011)
Previous data collected at this station seem to indicate that supplementary dietary trace minerals may be of value under certain feeding regimes. This trial also was designed to obtain further information on the value of shelter and concrete in feeding lots. The steers used in this study had been used in various pasture trials during the summer of 1960. After those trials were completed, the steers were fed an all-roughage maintenance ration until they were allotted to this study December 14, 1960.
Keywords: Beef; Salt; Steers; Shelter